2007
DOI: 10.1016/j.pain.2006.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of observational (behavioral) measures of pain for children and adolescents aged 3 to 18 years

Abstract: Observational (behavioral) scales of pain for children aged 3 to 18 years were systematically reviewed to identify those recommended as outcome measures in clinical trials. This review was commissioned by the Pediatric Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (www.immpact.org). In an extensive literature search, 20 observational pain scales were identified for review including behavior checklists, behavior rating scales, and global rating scales. These scales varied in their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
390
0
11

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 590 publications
(407 citation statements)
references
References 45 publications
6
390
0
11
Order By: Relevance
“…Most children as young as 5 years of age are capable of validly self-reporting at least current pain if presented with an age-appropriate pain scale (3). With children younger than 5 years, and those who have cognitive or verbal communication deficits, pain assessment is more challenging and requires selecting an observational measure of pain (4). The same pain scale should be used with the child each time to allow for longitudinal comparison.…”
Section: To the Editormentioning
confidence: 99%
“…Most children as young as 5 years of age are capable of validly self-reporting at least current pain if presented with an age-appropriate pain scale (3). With children younger than 5 years, and those who have cognitive or verbal communication deficits, pain assessment is more challenging and requires selecting an observational measure of pain (4). The same pain scale should be used with the child each time to allow for longitudinal comparison.…”
Section: To the Editormentioning
confidence: 99%
“…Other studies have also indicated that facial expressions have an important function in pain assessment since they are one of the most reliable behavioral indicators of pain. 3,40 Future studies of pain assessment during painful proce- In this review it was found that this scale meets the validity parameter, but this does not mean that, in prior studies, the scale has not met other psychometric parameters, such as reliability, sensitivity, specificity or applicability. This study has been used in studies of concurrent validity of new scales, which definitely suggests it has good psychometric qualities.…”
Section: Discussionmentioning
confidence: 95%
“…13,14 One review study of behavioral measures of pain assessment submitted certain scales to a rigorous review procedure and found their levels of clinical evidence. 40 The FLACC was recommended for postoperative pain assessment, the CHEOPS for preoperative and postoperative pain assessment, and the PPPM for postoperative pain assessment on hospital discharge: three scales widely used for pain assessment, according to the levels of clinical evidence given. 40 In contrast, the AHTPS and the TPPPS were scales whose levels of evidence compromise their clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29][30] However, the heterogeneity of physical and cognitive impairments associated with CP makes it difficult to assess chronic pain using a single standardized tool. [26][27][28][29][30][31][32] Further, barriers to assessment stem from a lack of awareness among health professionals of psychometrically sound tools and/or a lack of standardization within organizations for routine chronic pain assessment. [32][33][34] Although previous reviews have identified measures to inform clinical practice, the application to children with disabilities is lacking.…”
mentioning
confidence: 99%